Sensitive determination of norepinephrine, epinephrine, dopamine and 5‐hydroxytryptamine by coupling HPLC with [Ag(HIO6)2]5−–luminol chemiluminescence detection. (29th February 2016) - Wu, Dong; Xie, He; Lu, Haifeng; Li, Wei; Zhang, Qunlin
Abstract: Based on the enhancing effects of norepinephrine (NE), epinephrine (EP), dopamine (DA) and 5‐hydroxytryptamine (5‐HT) on the chemiluminescence (CL) reaction between [Ag(HIO6 )2 ] 5− and luminol in alkaline solution, a high‐performance liquid chromatography (HPLC) method with CL detection was explored for the sensitive determination of monoamine neurotransmitters for the first time. The UV–visible absorption spectra were recorded to study the enhancement mechanism of monoamine neurotransmitters on the CL of [Ag(HIO6 )2 ] 5− and luminol reaction. The HPLC separation of NE, EP, DA and 5‐HT was achieved with isocratic elution using a mixture of aqueous 0.2% phosphoric acid and methanol (5:95, v/v) within 11.0 min. Under the optimized conditions, the detection limits of NE, EP, DA, and 5‐HT were 4.8, 0.9, 1.9 and 2.3 ng/mL, respectively, corresponding to 17.6–96.0 pg for 20 μL sample injection. The recoveries of monoamine neurotransmitters in rat brain were >95.6% with the precisions expressed by RSD <5.0%. The validated HPLC‐CL method was successfully applied for the quantification of NE, EP, DA and 5‐HT in rat brain. This method has promising potential for some biological and clinical investigations focusing on the levels of monoamine neurotransmitters. Copyright © 2016 John Wiley & Sons, Ltd.